Literature Review Artikel: MANFAAT MINYAK ATSIRI PADA BERBAGAI BAGIAN TUMBUHAN - Fikayuniar, Lia; Audiny, Cindy; Ibrahim, Asshasyfa; Hidayat, Dhivira Azfari Pratama; Julianti, Dine; Ramadhani, Putri; Zaenudin, Rian Ahmad (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2024)
Essential oils are aromatic compounds naturally found in various parts and types of plants. This study aims to evaluate the benefits of essential oils extracted from different plant parts using various methods. The research was conducted through a literature review by analyzing data from multiple journal articles. The review revealed that essential oils extracted from different plant parts exhibit diverse compositions and benefits. Essential oil from the leaves of zodia (Evodia suaveolens), obtained through distillation, yielded 0.6471%, with 4(5H)-Benzofuranone identified as the main component through GC-MS analysis. Meanwhile, hydro-steam distillation of kaffir lime (Citrus hystrix) peel produced essential oil containing 25 components, primarily demonstrating antioxidant activity. Steam distillation of langsat (Lansium domesticum) fruit peel yielded essential oil with a 0.18% yield, comprising monoterpenoid and sesquiterpenoid compounds as its major components. This study highlights the potential of essential oils from various plant parts as sources of bioactive compounds with diverse benefits.